(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
The aim of this study was to inquire about the concept of "physical education class" students have undergraduate program in physical education and sport at the University of Quindio, which stems from the understanding of the concept of classes in the Students enrolled in semester 1 to 3 of our program, will serve as theoretical reference to leverage the academic processes of our program or plan curriculum, especially the search for the state of the art that always keeps us in debt and especially about of conception that they pose to our students of physical educationclass. This project is part of the field of university students as the population that is part of this study was aged between 15 and 19 years of age, so the notions or interpretations about the concept that students have in front a physical education class, help the breakdown of traditional conceptions of class and allowed the questioning of other sights to allow the class thought otherwise. In a context as is the University and in the ages at which developed the study, it is vitally important and current practices allow and recognize rethink concepts of those young people of our region in the field of physical education and sports taking the decision to participate in our academic life project.